Results of different kinds of carotid endarterectomy in patients with and without type 2 diabetes mellitus - А. N. Kazantsev; R. A. Vinogradov; M. A. Chernyavsky; V. N. Kravchuk; D. V. Shmatov; A. A. Sorokin; A. A. Erofeev; V. A. Lutsenko; R. V. Sultanov; A. R. Shabaev; I. M. Radjabov; G. Sh. Bagdavadze; et al. (Сахарный диабет)
BACKGROUND: Type 2 diabetes mellitus (DM) is one of the important markers for the development of adverse cardiovascular events after carotid endarterectomy (CEE). However, studies on this issue are based on small sample of patients and do not take into account the type of surgery as an additional factor of potentially negative impact on the course of the postoperative period.AIM: Analysis of hospital and long-term results of eversion and classical CEE with plastic surgery of the reconstruction zone with a biological patch in patients with type 2 diabetes and without it.MATERIALS AND METHODS: In this multicenter retrospective study from January 2010 to December 2020. included 5731 patients. Depending on the presence / absence of type 2 diabetes and the type of implemented CEE, 4 groups were formed: group 1 — 12.2% (n = 702) — patients with type 2 diabetes and eversion CEE; Group 2 — 55.0% (n = 3153) patients without type 2 diabetes and eversion CEE; Group 3 — 8.5% (n = 484) patients with type 2 diabetes and classical CEE; Group 4 — 24.3% (n = 1392) patients without type 2 diabetes and classical CEE. The duration of postoperative follow-up was 78.6 ± 39.2 months.RESULTS: At the long-term follow-up stage, patients with type 2 diabetes after the classical surgical technique demonstrated the highest rates of all types of complications: death (p <0.0001), MI (p = 0.011), ischemic stroke (p <0.0001), restenosis / occlusion of the ICA (p <0.0001), combined end point (p <0.0001). At the same time, the group of eversion CEE with impaired carbohydrate metabolism took the second position in terms of the prevalence of adverse events. These circumstances demonstrate that patch implantation is accompanied by an increased risk of developing not only myocardial infarction, but also restenosis of the reconstruction zone, as well as the associated ischemic stroke, which was demonstrated by our results.CONCLUSION: Patients with type 2 diabetes and a history of CEE are at increased risk of ischemic stroke at the hospital stage of observation and all unfavorable cardiovascular conditions (death, myocardial infarction, ischemic stroke, restenosis or ICA occlusion in the reconstruction zone) in the long-term postoperative period.